2017
DOI: 10.5114/aoms.2016.59710
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic investigations of PLA2G16 and CDH11 expression levels as independent prognostic markers of human osteosarcoma

Abstract: IntroductionThe aim of this study was to facilitate and deepen the understanding of the associations of the clinical significance of PLA2G16 and CDH11 in patients with osteosarcoma.Material and methodsWe collected 50 paired osteosarcoma tissues and adjacent normal bone tissues and evaluated the expression of PLA2G16 and CDH11 by quantitavise reverse transcriptase real-time polymerase chain reaction.ResultsPLA2G16 expression was upregulated in osteosarcoma tissues when compared with adjacent normal bone tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Increasing evidence has revealed that CDH11 plays a momentous role in the development of a broad series of human malignancies, and identified CDH11 as a functional tumour suppressor which is commonly silenced by promoter methylation 3. Previous studies have shown that CDH11 inhibits invasion and proliferation in head and neck cancer,21 osteosarcoma,8,22 glioma,23 melanoma24 and bladder cancer 25. The correlation between the function of CDH11 and related mechanisms in colorectal cancer remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has revealed that CDH11 plays a momentous role in the development of a broad series of human malignancies, and identified CDH11 as a functional tumour suppressor which is commonly silenced by promoter methylation 3. Previous studies have shown that CDH11 inhibits invasion and proliferation in head and neck cancer,21 osteosarcoma,8,22 glioma,23 melanoma24 and bladder cancer 25. The correlation between the function of CDH11 and related mechanisms in colorectal cancer remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite aggressive treatment, about a third of affected patients die of their disease. More recently [1], many novel targets have been identified and serve as independent prognostic markers of human osteosarcoma. Neoadjuvant chemotherapy followed by surgical resection and additional adjuvant chemotherapy are routine treatment of osteosarcoma and the 5-year-survival rate of patients is 60–70% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown a significant downregulation of CDH11 expression in osteosarcoma tissues, and its expression level is notably correlated with patient survival rate. This suggests that CDH11 is likely an independent prognostic factor associated with poorer overall survival in osteosarcoma patients [ [59] , [60] , [61] ].…”
Section: Tumormentioning
confidence: 99%